DC Motor Design and Characteristics Using Matlab - Shehab, Abdal-Razak; Al- Mussawy, Raed; Al-Majdi, Kadhum (Journal of Engineering and Sustainable Development, 2014)
The basic problem of this paper is building designing steps of direct current (D.C.) motor by using one of MATLAB software facilities called m-file. This will provide testing of motor characteristics and motor performance on model instead original. Program also be used for testing motor performances and for testing motor prototypes because it provides possibility of changing motor dimensions and parameters with acceptable given limit. This is especially desirable for large D.C. motors over 50 kW, because testing of motor for different kinds of load and testing motors dynamic can prevent some malfunctions and damages of motor. More about essential motor dimensions and parameters that are crucial for building a motor steps design will be discussed further in paper. Motor dimensions and parameters calculation in m-file which contains different kinds of core materials will be compared with motor theoretical calculation. This software can also be used to enhance teaching of D.C. motors course.